International health care reform : a legal, economic, and political analysis - Flood, Colleen M. (London ; New York : Routledge, 2000)
Examining the current wave of health care reform efforts, this book compares internal market reforms and managed competition reform. Particular attention is paid to the role of managed care in each. Based on an analysis of reforms in the U.K., New Zealand, the U.S., and the Netherlands, the study compares models in terms of accountability, flexibility, monopoly, and quality. The book explains the structure of health care systems, the proposed reforms, and the case for government intervention.
Includes bibliographical references (p. [287]-307) and index.
oif 04/08/16
Loan
Keywords: Health care reform; Cross-Cultural Comparison; Santé, Services de